2020
DOI: 10.21203/rs.3.rs-15862/v2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Longitudinal changes in EEG power, sleep cycles and behaviour in a tau model of neurodegeneration.

Abstract: BACKGROUND: Disturbed sleep is associated with cognitive decline in neurodegenerative diseases such as Alzheimer’s disease (AD) and frontotemporal dementia (FTD). The progressive sequence of how neurodegeneration affects aspects of sleep architecture in conjunction with behavioural changes is not well understood. METHODS: We investigated changes in sleep architecture, spectral power and circadian rhythmicity in the tet-off rTg4510 mouse overexpressing human P301L tau within the same subjects over time. Doxycyc… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…However, we found that VEP amplitude was robust, even in 8-months old Tau+ animals. Tau+ mice also have altered circadian rhythms, with increased periods of wakefulness, less time in nonrapid-eye-movement sleep (Holton et al, 2020), and altered sharp-wave ripple dynamics (Witton et al, 2016). These changes may contribute to the changes in long-term visual plasticity that we observed as sleep is important for SRP in mouse V1 (Aton et al, 2014; Cooke and Bear, 2010, 2012; Ji and Wilson, 2007).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, we found that VEP amplitude was robust, even in 8-months old Tau+ animals. Tau+ mice also have altered circadian rhythms, with increased periods of wakefulness, less time in nonrapid-eye-movement sleep (Holton et al, 2020), and altered sharp-wave ripple dynamics (Witton et al, 2016). These changes may contribute to the changes in long-term visual plasticity that we observed as sleep is important for SRP in mouse V1 (Aton et al, 2014; Cooke and Bear, 2010, 2012; Ji and Wilson, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have reported alterations in rTg4510 mouse behaviour: Tau+, and to a lesser extent, Tau-mice tend to show hyperactivity and motor stereotypy, whilst maintaining good motor coordination [16, 18, 19, 55, 61]. These mice do not appear to respond to novelty, and have impaired spatial working memory [16, 18].…”
Section: Discussionmentioning
confidence: 99%
“…The sleep-wake cycle has been examined across different pathological stages in various mouse models, including 3xTg-AD [ 233 , 234 ], APP/PS1 [ 234 , 235 ], Tg2576 [ 234 , 236 ], P301S Tau [ 237 ], rTG4510 [ 238 ], PLB1 Triple [ 239 ], and PLB2tau [ 240 ] models ( Table 3 ). Slow (<1 Hz) oscillations have been analysed together with delta oscillations (1–4 Hz), which can be used to determine NREM sleep.…”
Section: Slow Oscillations and Admentioning
confidence: 99%
“…Slow (<1 Hz) oscillations have been analysed together with delta oscillations (1–4 Hz), which can be used to determine NREM sleep. In several AD mouse models, NREM sleep is reduced and fragmented [ 233 , 234 , 237 , 238 ], which implies that changes also occur in the patterns of slow oscillations. It has been suggested that the reduction in GABAergic tone impairs long-range synchronous firing in an amyloid mouse model [ 92 ].…”
Section: Slow Oscillations and Admentioning
confidence: 99%
“…In preclinical mouse models of tauopathy, low frequency EEG oscillations are increased (Das et al, 2018), fMRI resting state networks are disrupted (Green et al, 2019), and coupling between hippocampal and prefrontal cortical local field potentials (LFPs) is disrupted (Ahnaou et al, 2017). In the well-characterized rTg4510 model of tauopathy, hippocampal LFP (Ciupek et al, 2015) and cortical EEG are disrupted (Holton et al, 2020), and strong low frequency oscillations emerge in LFP recordings from frontal cortex (Menkes-Caspi et al, 2015). (Menkes-Caspi et al, 2015).…”
Section: Introductionmentioning
confidence: 99%